المصطلح اللّسانيّ العرفانيّ بين التّرجمة المشرقيّة والتّرجمة المغاربيّة (دراسة وصفيّة مقارنة لنماذج مختارة): The Cognitive Linguistic Term between Eastern and Maghrebian Translations (A Descriptive Comparative Study of Selected Models) - Medallel , hadjer; badeeche , ammar (Maalim, 2024)
Cognitive linguistics is one of the latest and most fertile fields of study in linguistics. It entered Arabic culture through translation and authorship but arrived late compared to its emergence in Western studies in the 1970s. At this point, serious Arabic studies in cognitive linguistics began to appear, with researchers translating foreign works into Arabic to make them accessible to an Arabic-speaking audience. Others also initiated the creation of original Arabic-language books, enriching Arabic libraries today. However, despite these efforts, translating cognitive terms faces some challenges, which indicates a lack of unified efforts to establish a common terminology across Arab countries. This study aims to observe the similarities and differences between Eastern and Maghrebian Arab linguists in their approach to cognitive linguistic terminology through their contemporary linguistic contributions.